Method for manufacturing surface-treated metal sheet, surface-treated metal sheet, and laminated material

CN123022835APending Publication Date: 2026-10-30TOYO KOHAN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580024247.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-31
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0022]根据本发明,能够提供一种表面处理金属板的制造方法、表面处理金属板以及层叠材料,该制造方法能够抑制形成被覆层时的起泡发生,并且能够提供具备优异外观的层叠材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022835A_ABST
    Figure CN123022835A_ABST
Patent Text Reader

Abstract

Provided is a method for manufacturing a surface-treated metal sheet, including: a step of preparing a metal base material (10); a zinc phosphate treatment step of forming a zinc phosphate layer (20) on a surface of the metal base material (10); and a sealing step of forming a sealing layer (30) on the zinc phosphate layer (20), wherein the zinc phosphate layer (20) contains phosphorus at a content W(P) of 100 to 300 mg / m 2 , and the sealing layer (30) contains zirconium and a urethane-based resin, and has an adhesion amount W(R) of 60 to 700 mg / m 2 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing a surface-treated metal sheet, the surface-treated metal sheet, and the laminated material. Background Technology

[0002] Coated metal sheets with a resin coating are widely used in building exterior components, automotive components, etc., and are known for applications such as joint materials for seams (e.g., Patent Document 1). A surface-treated galvanized steel sheet is known to have a zinc phosphate coating and a resin layer formed on the galvanized steel sheet (e.g., Patent Document 1). As a surface-treated steel sheet suitable for use in automotive components, building materials, etc., a surface-treated steel sheet is known to have a zinc phosphate crystal layer (first layer) formed on the galvanized steel sheet and a resin-containing coating layer (second layer) (e.g., Patent Document 1). In Patent Document 1, the zinc phosphate crystal layer and the coating layer exhibit excellent adhesion due to the anchoring effect of the zinc phosphate crystals.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-155261 Summary of the Invention

[0006] The problem the invention aims to solve

[0007] However, because the zinc phosphate crystal layer is composed of multiple needle-like zinc phosphate crystals, the resin material cannot penetrate to the roots of the zinc phosphate crystals during the formation of the coating layer, sometimes creating voids within the zinc phosphate crystal layer. Therefore, the technology described in Patent Document 1 has the following problem: moisture entering these voids reacts with zinc, causing corrosion and generating gas, which may easily lead to blistering (expansion). If blistering occurs, the appearance of the surface-treated steel sheet deteriorates, or the surface-treated steel sheet is prone to corrosion from the blistering site, thus reducing corrosion resistance.

[0008] The purpose of this invention is to provide a method for manufacturing a surface-treated metal sheet, the surface-treated metal sheet, and a laminated material. This manufacturing method can suppress blistering during the formation of the coating layer and can provide a laminated material with excellent appearance.

[0009] Solution for solving the problem

[0010] [1] According to Embodiment 1 of the present invention, a method for manufacturing a surface-treated metal plate is provided, comprising: a step of preparing a metal substrate; a zinc phosphate treatment step of forming a zinc phosphate layer on the surface of the metal substrate; and a sealing step of forming a sealing layer on the zinc phosphate layer, wherein the phosphorus content W(P) contained in the zinc phosphate layer is 100~300 mg / m³. 2The sealing layer contains zirconium and urethane resin, and the adhesion amount W(R) of the sealing layer is 60~700 mg / m³. 2 .

[0011] [2] According to embodiment 2 of the present invention, a method for manufacturing a surface-treated metal plate according to embodiment 1 is provided, wherein the ratio of the phosphorus content W(P) in the zinc phosphate layer to the amount of the sealing layer W(R) "W(P) / W(R)" is 0.3 to 3.5.

[0012] [3] According to embodiment 3 of the present invention, a method for manufacturing a surface-treated metal sheet according to embodiment 1 or 2 is provided, wherein the step of preparing the metal substrate includes: forming a zinc plating layer on the surface of the metal substrate.

[0013] [4] According to embodiment 4 of the present invention, a method for manufacturing a surface-treated metal plate according to any one of embodiments 1 to 3 is provided, wherein the zirconium content W (Zr) of the surface-treated metal plate is 1.5 to 23.0 mg / m³. 2 .

[0014] [5] According to embodiment 5 of the present invention, a surface-treated metal plate is provided, comprising: a metal substrate, a zinc phosphate layer formed on at least one side of the metal substrate, and a sealing layer formed by laminating the zinc phosphate layer, wherein the phosphorus content W(P) contained in the zinc phosphate layer is 100~300 mg / m³. 2 The sealing layer is composed of a zirconium-containing urethane resin, and the adhesion amount W(R) of the sealing layer is 60~700 mg / m³. 2 .

[0015] [6] According to embodiment 6 of the present invention, a surface-treated metal plate according to embodiment 5 is provided, wherein the zirconium content W(Zr) is 1.5~23.0 mg / m³. 2 .

[0016] [7] According to embodiment 7 of the present invention, a surface-treated metal plate according to embodiment 5 or 6 is provided, wherein the ratio of the phosphorus content W(P) in the zinc phosphate layer to the amount of the sealing layer W(R) "W(P) / W(R)" is 0.3 to 3.5.

[0017] [8] According to embodiment 8 of the present invention, a surface-treated metal plate according to any one of embodiments 5 to 7 is provided, wherein the ratio of the phosphorus content W(P) in the zinc phosphate layer to the zirconium content W(Zr) "W(P) / W(Zr)" is 10 to 120.

[0018] [9] According to embodiment 9 of the present invention, a surface-treated metal sheet according to any one of embodiments 5 to 8 is provided, wherein the metal substrate comprises a metal base plate and a zinc-based zinc plating layer, and the zinc phosphate layer is formed on the zinc plating layer.

[0019]

[10] According to embodiment 10 of the present invention, a surface-treated metal sheet according to embodiment 9 is provided, wherein the zinc content W (Zn) in the galvanized layer is 3~30 g / m 2 .

[0020]

[11] According to embodiment 11 of the present invention, a laminated material is provided, comprising: a surface-treated metal plate of any one of embodiments 5 to 10, and a coating layer made of resin material and formed on the closed layer.

[0021] The effects of the invention

[0022] According to the present invention, a method for manufacturing a surface-treated metal sheet, a surface-treated metal sheet, and a laminated material can be provided. The manufacturing method can suppress blistering during the formation of the coating and can provide a laminated material with excellent appearance. Attached Figure Description

[0023] Figure 1 This is a schematic cross-sectional view showing the structure of the surface-treated metal plate in an embodiment of the present invention.

[0024] Figure 2 yes Figure 1 Enlarged view of Part II.

[0025] Figure 3 This is a schematic cross-sectional view showing the structure of the laminated materials in an embodiment of the present invention. Detailed Implementation

[0026] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings.

[0027] <Surface-treated metal sheet 1>

[0028] Figure 1 This is a schematic cross-sectional view showing the structure of the surface-treated metal plate 1 in this embodiment. Figure 2 yes Figure 1 Enlarged view of Part II Figure 3 This is a schematic cross-sectional view showing the structure of the laminated material 100 in this embodiment. The surface-treated metal plate 1 in this embodiment includes a metal substrate 10, a zinc phosphate layer 20 disposed on the metal substrate 10, and a sealing layer 30 disposed on the zinc phosphate layer 20. (As shown...) Figure 3 As shown, the surface-treated metal plate 1 is suitable for use as a laminated material 100 formed by forming a resin-based coating layer 40 on the sealing layer 30. Hereinafter, it will be mainly used... Figure 1 and Figure 2 The structure of the surface-treated metal plate 1 will be described.

[0029] <Metal Substrate 10>

[0030] In this embodiment, the metal substrate 10 is a plate having a metal base plate 11 and a zinc-containing galvanized layer 12 formed on the metal base plate 11.

[0031] The metal base plate 11 is not particularly limited, but iron or aluminum-based metal base plates can be used. For iron-based metal base plates 11, carbon steel plates or stainless steel plates can be used. For carbon steel plates, plates composed of low-carbon steel (0.01-0.15% by weight carbon content), extremely low-carbon steel (less than 0.01% by weight carbon content), or non-aging carbon steel made by adding Ti, Nb, etc., to extremely low-carbon steel can be used. When using steel plates as the metal base plate 11, it is preferable to use hot-rolled plates of these steels that have been pickled to remove surface oxide scale (oxide film), then cold-rolled, followed by electrolytic cleaning, annealing, and surface finishing. The annealing method can be either continuous annealing or box annealing, without particular limitation.

[0032] The thickness of the metal base plate 11 in this embodiment is not particularly limited, but it is preferably 0.04~2.00mm, and more preferably 0.04~1.50mm.

[0033] The zinc plating layer 12 is a zinc-containing layer provided on the metal base plate 11, and in the case of an alloy, it comprises a zinc-based alloy. Examples of metals constituting the zinc plating layer 12 include zinc, zinc-cobalt-molybdenum alloys, zinc-cobalt alloys, zinc-nickel alloys, zinc-iron alloys, alloyed hot-dip galvanized metals, and zinc-aluminum-magnesium alloys. Among these zinc-based plating metals, from the viewpoint of improving the corrosion resistance of the surface-treated metal plate 1, zinc-cobalt-molybdenum alloys or pure zinc (hereinafter also referred to as pure zinc) with a zinc weight ratio of 99.9% or more are more preferred. The zinc plating layer 12 can be formed by electroplating the surface of the metal base plate 11 using a plating bath with a specified composition.

[0034] The zinc content (W(Zn)) in the zinc plating layer 12 is preferably 3~30 g / m 2 More preferably 5~20g / m 2 It should be noted that the zinc content W(Zn) represents the amount in one surface of the metal base plate 11.

[0035] The thickness of the zinc plating layer 12 is not particularly limited, but is preferably 0.3 to 8.0 μm. The thicker the zinc plating layer 12, the smoother the surface roughness, which may affect the formation of the subsequent zinc phosphate layer 20. Especially in the case of zinc-based plating, crystals precipitate in a plate-like manner, thus there is a tendency for the surface roughness of the zinc plating layer 12 to become smoother. Therefore, from the viewpoint of suppressing the reduction in surface roughness, the thickness of the zinc plating layer 12 is more preferably 0.3 to 5.0 μm. From the viewpoint of corrosion resistance, it is further preferably 0.6 to 5.0 μm. From the viewpoint of more preferably balancing corrosion resistance and suppressing the reduction in surface roughness caused by zinc plating, the thickness of the zinc plating layer 12 is particularly preferably 0.7 μm to 4.5 μm.

[0036] It should be noted that in this embodiment, a galvanized layer 12 is formed on both sides of the metal base plate 11, but the metal substrate 10 is not particularly limited to this, and a galvanized layer 12 may be formed only on one side of the metal base plate 11. Alternatively, the metal substrate 10 may not have a galvanized layer 12 and may consist only of the metal base plate 11.

[0037] <Zinc phosphate layer 20>

[0038] The zinc phosphate layer 20 is a layer containing zinc phosphate crystals formed on both sides of the metal substrate 10. The zinc phosphate layer 20 is formed to improve the adhesion (hereinafter also referred to as coating adhesion) of the surface-treated metal plate 1 to the resin material (coating layer 40). The zinc phosphate crystals include needle-like or scaly shapes; from the viewpoint of improving coating adhesion, it is preferable to include needle-like zinc phosphate crystals. In this embodiment, the zinc phosphate layer 20 is formed on both sides of the metal substrate 10, but it is not particularly limited thereto; the zinc phosphate layer 20 may also be formed on only one side of the metal substrate 10.

[0039] The phosphorus content (W(P)) in zinc phosphate layer 20 is 100~300 mg / m³. 2 The preferred concentration is 120~280 mg / m³. 2 More preferably 160~250 mg / m 2 By setting the phosphorus content W(P) within the aforementioned range, combined with the control of the sealing layer 30, the adhesion to the resin material (coating layer 40) can be ensured, and foaming can be suppressed. If the phosphorus content W(P) is too low, the adhesion of the coating layer will decrease; conversely, if the phosphorus content W(P) is too high, the resin will have difficulty penetrating to the roots of the zinc phosphate crystals during the sealing process, which may easily lead to foaming. The phosphorus content W(P) can be determined by fluorescence X-ray analysis. It should be noted that the phosphorus content W(P) represents the amount in one facet of the metal substrate 10.

[0040] The zinc phosphate layer 20 may contain zirconium, titanium dioxide, aluminum oxide, calcium carbonate, talc, silicon dioxide, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc., as other inorganic components within the zinc phosphate crystals. More preferably, it contains zirconium. The zirconium content in the zinc phosphate layer 20 is preferably 0.01 mg / m³. 2 Above and less than 1 mg / m 2 .

[0041] <Closed layer 30>

[0042] The sealing layer 30 is a layer containing urethane resin and zirconium. The sealing layer 30 is formed to prevent moisture from penetrating from the outside into the zinc phosphate layer 20. In this embodiment, the sealing layer 30 is formed on both sides of the zinc phosphate layer 20 formed on the metal substrate 10, but it is also possible to form the sealing layer 30 on only one side of the zinc phosphate layer 20.

[0043] The urethane resin contained in the sealing layer 30 is a reaction product of a polyol and a polyisocyanate. Examples of polyols include polyacrylic acid polyols, polyester polyols, polyether polyols, and other high-molecular-weight polyols. Examples of polyisocyanates include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, and aromatic aliphatic diisocyanates. With the sealing layer 30 as a whole, the content of the urethane resin in the sealing layer 30 is preferably 85% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more.

[0044] The adhesion amount W(R) of sealing layer 30 is 60~700 mg / m³ 2 From the perspective of more stably balancing the suppression of foaming and the improvement of the adhesion of the coating layer, a concentration of 60~500 mg / m³ is preferred. 2 More preferably 70~240 mg / m³ 2 More preferably 75~200mg / m 2By setting the sealing layer 30 as a layer containing urethane resin and zirconium, setting the adhesion amount W(R) of the sealing layer 30 within the aforementioned range, and combining this with the control of the phosphorus content W(P) of the zinc phosphate layer 20, it is possible to ensure the adhesion of the resin material (coating layer 40) and suppress blistering. If the adhesion amount W(R) of the sealing layer 30 is too small, the voids at the root of the zinc phosphate layer 20 cannot be filled, resulting in difficulty in suppressing blistering. On the other hand, if the adhesion amount W(R) is too large, when the coating layer 40 is formed on the surface-treated metal plate 1 to produce the laminated material 100, the stress generated in the sealing layer 30 during the baking process after the resin material is coated may be released during the cooling after baking. As a result, the sealing layer 30 shrinks while encasing the zinc phosphate layer 20, and new voids may be generated between the sealing layer 30 and the metal substrate 10, or between the zinc phosphate layer 20 and the metal substrate 10. Thus, if the amount of the sealing layer 30 adhering to it is too large, blistering may easily occur due to the voids generated at any interface of the laminated material 100 after the baking process. It should be noted that the amount of the sealing layer 30 adhering to it, W(R), represents the amount of adhering to one surface of the metal substrate 10.

[0045] It should be noted that, in Figure 1 In order to make the manufacturing process sequence easier to understand, the diagram shows a sealing layer 30 stacked on top of a zinc phosphate layer 20. However, since the zinc phosphate layer 20 contains needle-like or scaly zinc phosphate crystals, the actual arrangement is as follows: Figure 2 As shown, the sealing layer 30 is configured to penetrate to the root of the zinc phosphate crystals through the regions between the zinc phosphate crystals constituting the zinc phosphate layer 20. Furthermore, the sealing layer 30 can contact the zinc plating layer 12 of the metal substrate 10 between the roots of the zinc phosphate crystals. The sealing layer 30 may completely cover each zinc phosphate crystal, or it may not cover a portion such as the upper or side parts of the zinc phosphate crystals, but it is preferable to cover the roots of the zinc phosphate crystals. In this way, the sealing layer 30 penetrates into the interior of the zinc phosphate layer 20, filling the space between the roots of the zinc phosphate crystals constituting the zinc phosphate layer 20. This inhibits the penetration of moisture from the outside into the interior of the zinc phosphate layer 20. Therefore, when the surface-treated metal plate 1 of this embodiment is laminated with resin material (coating layer 40) to form a laminated material 100, corrosion and gas generation caused by moisture penetration can be suppressed, and blistering can be inhibited.

[0046] The inventors have discovered that, when using conventional surface-treated metal sheets with a zinc phosphate layer, blistering occurs after the formation of a coating containing resin material due to voids at the interfaces of the layers constituting the surface-treated metal sheet or within the layers. Through further repeated experiments to suppress blistering, the inventors concluded that there are two modes of void formation. As a first mode, in conventional surface-treated metal sheets with only a zinc phosphate layer and no sealing layer, the resin material has difficulty penetrating the spaces between the zinc phosphate crystals, thus leaving voids at the roots of the zinc phosphate layer. The inventors found that by forming a predetermined sealing layer 30 on the zinc phosphate layer 20, allowing the sealing layer 30 to penetrate the spaces between the zinc phosphate crystals, voids are prevented from forming at the roots of the zinc phosphate layer 20, thereby solving the aforementioned problem.

[0047] As a second model, one can exemplify the following: the stress in the resin material generated during the baking process of the coating layer containing resin material formed on the surface of the surface-treated metal sheet is released upon cooling, thereby creating voids at any interface of the laminated materials after the baking process. Furthermore, it is known that even in conventional cases where a sealing layer is formed on a surface-treated metal sheet with a zinc phosphate layer and no voids are formed at the root of the zinc phosphate layer, new voids sometimes arise between the sealing layer and the metal sheet, or between the zinc phosphate layer and the metal sheet, during the baking process of the coating layer formation process. The inventors have determined that the reason for this second model is that, similar to the stress generated in the coating layer due to baking, stress is generated within the sealing layer during the baking process, and the release upon cooling causes the sealing layer to shrink while encapsulating the zinc phosphate layer. Furthermore, the inventors have found that this phenomenon of stress generation within the sealing layer occurs when materials constituting the sealing layer, such as phenolic resins or silicone resins, are selected, or when an excessive amount of urethane resin is selected, or when zirconium is not present. Furthermore, the inventors have discovered that by setting the sealing layer 30 to a layer containing urethane resin and zirconium, setting the amount of the sealing layer 30 attached W(R) to the above-mentioned range, and combining this with the control of the phosphorus content W(P) of the zinc phosphate layer, it is possible to significantly suppress the formation of voids during coating and the formation of voids after the baking process.

[0048] The zirconium content in the sealing layer 30 is preferably 1.5~23.0 mg / m³. 2 More preferably 1.8~10 mg / m³ 2 More preferably, it is 1.8~6.0 mg / m³. 2By including zirconium in the sealing layer 30 within the aforementioned range, the adhesion between the surface-treated metal plate 1 and the resin material (coating layer 40) can be improved. It should be noted that the zirconium content of the sealing layer 30 refers to the amount in one side of the metal substrate 10.

[0049] In addition to zirconium, the sealing layer 30 may also contain other inorganic components, such as titanium dioxide, aluminum oxide, calcium carbonate, talc, silicon dioxide, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, and calcium phosphate.

[0050] The zirconium content W(Zr) of the surface-treated metal plate 1 is expressed as the amount of zirconium attached per unit area relative to the metal substrate 10, and is preferably 1.5~23.0 mg / m². 2 More preferably 1.8~11 mg / m³ 2 More preferably, it is 2.0~6.0 mg / m³. 2 It should be noted that when both the zinc phosphate layer 20 and the sealing layer 30 contain zirconium, the zirconium content W(Zr) of the surface-treated metal plate 1 is the total zirconium content contained in the zinc phosphate layer 20 and the sealing layer 30. By setting the zirconium content W(Zr) within the above range, the bubbling suppression effect of the surface-treated metal plate 1 can be improved. Furthermore, the adhesion to the resin material (coating layer 40) can be improved. It should be noted that the zirconium content W(Zr) represents the amount in one surface of the metal substrate 10.

[0051] The ratio of phosphorus content W(P) in the zinc phosphate layer 20 to the amount W(R) of the sealing layer 30, "W(P) / W(R)", is preferably 0.3 to 3.5, more preferably 0.4 to 3.0, and even more preferably 1.0 to 3.0. By setting "W(P) / W(R)" within the above range to achieve a balance control between the sealing layer 30 and the zinc phosphate layer 20, the surface-treated metal plate 1 can achieve the following: the sealing layer 30 fills the root of the zinc phosphate layer 20, reducing voids, and the unevenness formed on the surface by the zinc phosphate crystals is not excessively filled by the sealing layer 30 and is thus preserved. As a result, when resin material (coating layer 40) is laminated on the surface-treated metal plate 1, the adhesion of the coating layer can be improved, and the generation of bubbles can be further suppressed.

[0052] The ratio of phosphorus content W(P) in zinc phosphate layer 20 to the total zirconium content W(Zr) in zinc phosphate layer 20 and sealing layer 30, "W(P) / W(Zr)", is preferably 10 to 120, more preferably 15 to 100, and even more preferably 40 to 80. By controlling "W(P) / W(Zr)" within the above range, when laminating resin material (coating layer 40) on surface-treated metal plate 1, it is possible to improve the adhesion of the coating layer while further suppressing the generation of bubbles.

[0053] <Manufacturing Method of Surface-treated Metal Plate 1>

[0054] The surface-treated metal plate 1 in this embodiment can be manufactured by a method comprising the following steps: a step of preparing a metal substrate 10, a zinc phosphate treatment step of forming a zinc phosphate layer 20 on the surface of the metal substrate 10, and a sealing step of forming a sealing layer 30 on the zinc phosphate layer 20.

[0055] In the process of preparing the metal substrate 10, the aforementioned metal base plate 11 is prepared, and a zinc plating layer 12 is formed on the metal base plate 11 as needed. The metal plating conditions can be appropriately selected according to the desired composition of the zinc plating layer 12.

[0056] For example, when the zinc plating layer 12 is composed of a zinc-cobalt-molybdenum alloy, it can be formed by electroplating using a plating bath composed of 150-300 g / L zinc sulfate, 5-60 g / L cobalt sulfate, 0.01-0.5 g / L ammonium molybdate, 5-60 g / L ammonium sulfate, and less than 50 g / L sodium sulfate. The preferred electroplating conditions are pH 2.0-4.5, bath temperature 30-60°C, and current density 5-50 A / dm³. 2 .

[0057] When the zinc plating layer 12 is composed of a zinc-cobalt-molybdenum alloy, the preferred proportions of zinc, cobalt, and molybdenum in the zinc plating layer 12 are 0.1 to 5% by weight for cobalt, 0.001 to 1% by weight for molybdenum, with the balance being zinc. The proportions of the metals contained in the zinc plating layer 12 can be adjusted by setting the composition of the plating bath and the electroplating conditions to appropriate ranges.

[0058] Alternatively, for example, when the zinc plating layer 12 is composed of pure zinc, it can be formed by electroplating using a plating bath composed of 150-300 g / L zinc sulfate and 10-100 g / L sodium sulfate. The preferred electroplating conditions are pH 0.5-3.0, bath temperature 30-60°C, and current density 5-80 A / dm³. 2 .

[0059] In the zinc phosphate treatment process, a zinc phosphate layer 20 containing zinc phosphate crystals is formed on the surface of the aforementioned metal substrate 10. Specifically, the metal substrate 10 undergoes surface conditioning as a pretreatment, is immersed in a zinc phosphate treatment solution containing zinc phosphate crystals as a formal treatment, and then washed and dried, thereby forming the zinc phosphate layer 20. Surface conditioning can be performed using known surface conditioning agents containing Ti colloid or zinc phosphate colloid. The zinc phosphate treatment solution may also contain fluorosilicic acid as an etchant, zinc nitrate as an accelerator, and zirconium as an inorganic component.

[0060] As a zinc phosphate treatment solution, commercially available products can be used, such as Palbond (registered trademark) and ENALSESS (registered trademark) manufactured by Nippon Paint Surf Chemicals Co., Ltd., and SURFDINE (registered trademark) manufactured by Nippon Paint Surf Chemicals Co., Ltd.

[0061] The amount of phosphorus adhering to the metal substrate 10 during the zinc phosphate treatment process, i.e., the phosphorus content W(P) in the zinc phosphate layer 20, is 100~300 mg / m³. 2 The preferred concentration is 150~250 mg / m³. 2 Furthermore, in the zinc phosphate treatment process, if the treatment solution contains zirconium, the zirconium content in the formed zinc phosphate layer 20 is preferably set to 0.01 mg / m³. 2 Above and less than 1 mg / m 2 .

[0062] Next, in the sealing process, a sealing layer 30 is formed on the metal substrate 10 on which the zinc phosphate layer 20 is formed. Specifically, the surface of the zinc phosphate layer 20 is impregnated or coated with an aqueous dispersion (sealing solution) containing urethane resin and zirconium by roller, and then dried to form the sealing layer 30. The drying temperature also depends on the type of resin, but is preferably 80 to 150°C.

[0063] The concentration of solid components (concentration of urethane resin) in the sealing treatment solution is preferably 3 to 40% by weight, more preferably 3 to 30% by weight, and even more preferably 4 to 20% by weight.

[0064] The pH of the sealing treatment solution is preferably 3 to 11, more preferably 4 to 10. In addition, the viscosity of the sealing treatment solution at 20°C is preferably 0.5 to 3.0 mPa·s, more preferably 1.0 to 2.0 mPa·s, and even more preferably 1.2 to 1.8 mPa·s.

[0065] The zirconium content of the sealing solution is preferably 1.0~5.0 g / L. By setting the zirconium content of the sealing solution within the above range, when coating the sealing layer 30 of the obtained surface-treated metal plate 1, the zirconium content W(Zr) can be appropriately controlled within a range that facilitates the formation of the sealing layer 30, and the sealing layer 30 can be buried at the root of the zinc phosphate layer 20. This can further improve the adhesion of the surface-treated metal plate 1 to the resin material (coating layer 40) and suppress blistering.

[0066] The sealing solution may also contain a crosslinking agent. When a crosslinking agent is present, a crosslinked structure can be introduced by crosslinking the urethane resin particles, thereby improving the adhesion durability of the surface-treated metal plate 1 to the resin material (coating layer 40). As a crosslinking agent, crosslinking agents containing amino, oxazoline, epoxy, carbodiimide, etc., can be used.

[0067] The adhesion amount W(R) of the sealing layer 30 in the sealing process is 60~700 mg / m³. 2 Preferably 60~500mg / m 2 More preferably 70~240 mg / m³ 2 By setting the amount of the sealing layer 30 attached, W(R), within the above-mentioned range, it is possible to suppress the generation of bubbles when the resin material (coating layer 40) is formed on the surface-treated metal plate 1.

[0068] Furthermore, the ratio of phosphorus content W(P) in the zinc phosphate layer 20 to the amount of phosphorus W(R) attached to the sealing layer 30, "W(P) / W(R)", is preferably 0.3 to 3.5, more preferably 0.4 to 3.0, and even more preferably 1.0 to 3.0. By setting "W(P) / W(R)" within the above range, foaming can be further suppressed.

[0069] The ratio of phosphorus content W(P) in zinc phosphate layer 20 to the total zirconium content W(Zr) in zinc phosphate layer 20 and sealing layer 30, "W(P) / W(Zr)", is preferably 10 to 120, more preferably 15 to 100, and even more preferably 40 to 80. By controlling "W(P) / W(Zr)" within the above range, when laminating resin material (coating layer 40) on surface-treated metal plate 1, it is possible to improve the adhesion of the coating layer while further suppressing the generation of bubbles.

[0070] As described above, the surface-treated metal sheet 1 of this embodiment can be manufactured. The surface-treated metal sheet 1 obtained in this way improves the adhesion to the resin material (coating layer 40) through the zinc phosphate layer 20, and suppresses the formation of voids within the zinc phosphate layer 20 through the sealing layer 30, thus suppressing blistering during the lamination of the resin material (coating layer 40). In components used in humid environments, especially high-temperature humid environments or under pressure (e.g., gasket components in piping), moisture and humidity penetrate the resin and reach between the resin and the surface-treated metal sheet. When the surface of the metal sheet is in a corrosive environment, blistering is easily generated. Similarly, when the resin on the surface of the laminated material has defects, the surface of the metal sheet is also easily placed in a corrosive environment. In this case, if voids exist between the resin and the surface-treated metal sheet, it is particularly easy to become a corrosive environment, promoting blistering. In contrast, the surface-treated metal sheet 1 of this embodiment suppresses the formation of voids within the zinc phosphate layer 20, thus significantly suppressing the surface of the metal substrate 10 from becoming a corrosive environment. Therefore, the surface-treated metal plate 1 of this embodiment enables the laminated material 100 formed by laminating a coating layer 40 containing resin material to have a good appearance. Furthermore, it can suppress leakage caused by bubbling, i.e., the outflow of gas or liquid from the voids formed by bubbling, thus suppressing the reduction of corrosion resistance. In addition, the laminated material 100 obtained using the surface-treated metal plate 1 of this embodiment suppresses bubbling, has an excellent appearance, and suppresses the reduction of corrosion resistance; therefore, it is suitable for use as a water system piping component, an interior or exterior architectural decorative component, an outdoor electrical component, an automotive exterior component, an automotive interior component, a gasket material, or a bearing material.

[0071] The resin material used as the coating layer 40 laminated on the surface-treated metal plate 1 is not particularly limited, but examples include phenolic epoxy resins and ethylene-vinyl acetate resins. It should be noted that the coating layer 40 can be formed directly on the surface-treated metal plate 1, or the coating layer 40 can be formed by depositing an adhesive resin on the surface-treated metal plate 1 and then using the adhesive resin. Examples of such adhesive resins include olefinic resins such as polyethylene, polypropylene, ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-acrylate copolymers, ethylene-acrylic acid copolymers, and ethylene-methacrylic acid copolymers, as well as urethane resins.

[0072] Example

[0073] The present invention will be described in more detail below with examples and comparative examples, but the present invention is not limited to these examples.

[0074] <Phosphorus adhesion W(P) and zirconium content W(Zr)>

[0075] For the surface-treated metal plate 1 obtained in each embodiment, the phosphorus adhesion amount W(P), zirconium content W(Zr), and zinc adhesion amount were determined by measuring with a fluorescence X-ray analysis device. A ZSX100e (manufactured by Rigaku Corporation) was used as the fluorescence X-ray analysis device. The fluorescence X-ray measurement confirmed that the metal elements contained in the surface-treated layer of the surface-treated metal plate 1 could be quantified using a calibration curve method. It should be noted that, here, the surface-treated layer refers to all layers formed on the steel plate in the surface-treated metal plate 1 of each embodiment (i.e., the zinc phosphate layer 20 and the sealing layer 30).

[0076] <Sealing layer adhesion amount W(R)>

[0077] For the surface-treated metal plate 1 obtained in each embodiment, the weight of the metal plate before and after the sealing process is measured, and the difference is calculated as the amount of sealing layer adhesion, thereby determining the amount of sealing layer 30 adhesion W(R).

[0078] <Appearance Evaluation>

[0079] The obtained surface-treated metal plate 1 was coated with a phenolic epoxy solvent (TOYOCHEM Co., Ltd. E-361-1) and dried at 205°C for 10 minutes, thereby forming a 15 μm coating layer 40 on the surface of the surface-treated metal plate 1, resulting in a laminated material 100. A vapor exposure test was conducted on the laminated material 100 at a temperature of 146°C and a relative humidity of 100% Rh for 168 hours. Then, the surface of the laminated material 100 was observed using an optical microscope, and the number of bubbles with a diameter of 10 μm or larger in a 1 mm (longitudinal) × 0.7 mm (transverse) area of ​​the optical microscope image was counted and evaluated as follows.

[0080] A: 0~1 (almost no bubbles)

[0081] B: 2-4 (less foam)

[0082] C: 5-19 (slightly more bubbles)

[0083] D: 20 or more (produces a lot of bubbles)

[0084] E: There are more than 20 bubbles with a diameter of 20μm or larger (there are a lot of bubbles, and some of them are large).

[0085] <Resin Adhesion>

[0086] The obtained surface-treated metal sheet 1 was hot-pressed with vinyl acetate resin, and a T-peel test (hereinafter also referred to as peel test) was performed according to JIS K 6854-3 to determine the peel strength of the surface-treated metal sheet 1 relative to the vinyl acetate resin. Specifically, two surface-treated metal sheets 1 with a width of 25 mm and a length of 80 mm were arranged opposite each other, and vinyl acetate resin (trade name Melthene, manufactured by Tosoh Corporation) was sandwiched between the two surface-treated metal sheets 1. The surface-treated metal sheet 1 and the vinyl acetate resin were hot-pressed together at a temperature of 150°C, a pressure of 0.5 MPa, and a time of 2 minutes to obtain a laminate material 100. For the prepared laminate material 100, a peel test was performed using a tensile testing machine (product name "AGX-V", manufactured by Shimadzu Corporation) at a peel speed of 200 mm / min to determine the maximum peel strength [unit: N / 20 mm]. If the maximum peel strength is above 5 N / 20 mm, it can be judged that the resin has excellent adhesion and that there is no significant reduction in adhesion caused by the formation of the sealing layer 30.

[0087] <Example 1>

[0088] As the metal base plate 11, a cold-rolled sheet of low-carbon aluminum-killed steel (0.2 mm thick) is prepared. Next, the metal base plate 11 is subjected to alkaline electrolytic degreasing and sulfuric acid impregnation pickling, followed by a bath temperature of 40°C and a current density of 15 A / dm³. 2 Under the specified conditions, plating was carried out, resulting in a metal substrate 10 with a zinc-cobalt-molybdenum alloy plating layer 12 formed on both sides of the metal base plate 11. The composition ratio of the zinc-cobalt-molybdenum alloy plating layer 12 was determined using a fluorescence X-ray analysis device. The results showed that Co: 0.16 wt%, Mo: 0.02 wt%, with the balance being Zn, and the zinc content W(Zn) was 10 g / m³. 2 .

[0089] Next, the metal substrate 10 is sequentially immersed in a surface conditioner and a zinc phosphate treatment solution, then washed with water and dried, thereby forming a zinc phosphate layer 20 on both sides of the metal substrate 10. The surface conditioner and zinc phosphate treatment solution are substances with the following properties.

[0090] {Surface Conditioner (Pretreatment)}

[0091] Bath ingredients: PREPARENE (manufactured by PARCase Sei Co., Ltd., Japan) 4g / L

[0092] Bath temperature: 50℃

[0093] pH: 6.0~9.0

[0094] {Zinc phosphate treatment solution (formal treatment)}

[0095] Bath ingredients: Palbond (manufactured by Japan's Palbond Seisei Co., Ltd.) 50g / L

[0096] Bath temperature: 50℃

[0097] pH: 2.0~3.0

[0098] Next, an aqueous dispersion containing urethane resin and zirconium (solids concentration 7 wt%, viscosity 1.6 mPa·s at 20°C, pH 6.5, zirconium content 2.6 g / L) was coated onto the zinc phosphate layer 20 using a roller coater and dried at 100°C for 2 seconds, thereby forming a sealing layer 30. The adhesion amount W(R) of the sealing layer 30 was set to 100 mg / m³. 2 As described above, a surface-treated metal plate 1 was obtained. The obtained surface-treated metal plate 1 was evaluated using the method described above. The results are shown in Table 1. It should be noted that, as described below, the formation conditions of the zinc phosphate layer 20 were set to be the same in all Examples 1-4 and Comparative Examples 1-10. Therefore, the zirconium content in the sealing layer 30 of Example 1 was calculated by subtracting the zirconium content W(Zr) in the surface-treated layer of Example 1 (i.e., the zirconium content in the zinc phosphate layer 20 where the sealing layer 30 was not formed) from the zirconium content W(Zr) in the surface-treated layer of Example 1. In the subsequent examples and comparative examples, the zirconium content in the sealing layer 30 was also calculated using the same method.

[0099] <Examples 2-4, Comparative Examples 3-4>

[0100] The amount of the sealing layer 30 attached, W(R), was changed to the value recorded in Table 1. Otherwise, the surface-treated metal plate 1 was obtained in the same manner as in Example 1, and the evaluation was performed in the same manner. The results are shown in Table 1.

[0101] <Comparative Example 1>

[0102] For the metal substrate 10 with the zinc phosphate layer 20 formed, no sealing treatment was performed. Otherwise, a surface-treated metal plate was obtained in the same manner as in Example 1, and the evaluation was carried out in the same manner. The results are shown in Table 1.

[0103] <Comparative Example 2>

[0104] During the sealing process, an aqueous dispersion containing phenolic resin (solids concentration 13% by weight, viscosity 1.9 mPa·s at 20°C, pH 4.0) was used instead of an aqueous dispersion containing urethane resin. Otherwise, the surface-treated metal plate was obtained in the same manner as in Example 1, and the evaluation was performed in the same manner. The results are shown in Table 1.

[0105] <Comparative Examples 5-8>

[0106] During the sealing process, an aqueous dispersion containing an organosilicon resin was used instead of an aqueous dispersion containing a urethane resin, and the amount of sealing layer W(R) was changed to the value described in Table 1. Otherwise, a surface-treated metal plate was obtained in the same manner as in Example 1, and the evaluation was performed in the same manner. The results are shown in Table 1.

[0107] <Comparative Examples 9-10>

[0108] During the sealing process, an aqueous dispersion containing urethane resin and free of zirconium (solids concentration 7 wt%, viscosity 1.6 mPa·s at 20°C, pH 6.5) was used, and the sealing layer adhesion amount W(R) was changed to the value described in Table 1. Otherwise, the surface-treated metal sheet was obtained in the same manner as in Example 1, and the evaluation was performed in the same manner. The results are shown in Table 1.

[0109] [Table 1]

[0110]

[0111] As shown in Table 1, the surface-treated metal plates 1 in Examples 1-4 have a zinc phosphate layer 20 and a sealing layer 30 containing zirconium and urethane resin, with a phosphorus content W(P) of 100-300 mg / m³. 2 The adhesion amount of the sealing layer, W(R), is 60~700 mg / m³. 2 These materials suppress the formation of bubbles during the formation of the coating layer 40 containing the resin material, and also provide excellent adhesion to the resin material (coating layer 40). In particular, in Examples 1 and 2, where the ratio of the phosphorus content W(P) in the zinc phosphate layer 20 to the amount of the sealing layer W(R) "W(P) / W(R)" was appropriately controlled, the formation of bubbles was significantly suppressed.

[0112] On the other hand, the surface-treated metal plates of Comparative Example 1 (which does not have a sealing layer), Comparative Example 2 (which uses a phenolic resin as a sealing layer), Comparative Examples 3 and 4 (which have a sealing layer adhesion amount W(R) outside a specific range), Comparative Examples 5 to 8 (which use an organosilicon resin as a sealing layer), and Comparative Examples 9 and 10 (which use a zirconium-free urethane resin as a sealing layer) all resulted in a large amount of bubbling when the resin materials were laminated.

[0113] Explanation of reference numerals in the attached figures

[0114] 1…Surface-treated metal sheet

[0115] 10…Metal substrate

[0116] 11…Metal base plate

[0117] 12…Zinc plating layer

[0118] 20… Zinc phosphate layer

[0119] 30…closed layer

[0120] 100…Layered materials

[0121] 40…Covering layer

Claims

1. A method for manufacturing a surface-treated metal sheet, comprising: The process of preparing the metal substrate; A zinc phosphate treatment process for forming a zinc phosphate layer on the surface of the metal substrate; and The sealing process of forming a sealing layer on the zinc phosphate layer, The phosphorus content (W(P)) in the zinc phosphate layer is 100~300 mg / m³. 2 , The sealing layer contains zirconium and urethane resin. The adhesion amount W(R) of the sealing layer is 60~700 mg / m³. 2 .

2. The method for manufacturing a surface-treated metal plate according to claim 1, wherein, The ratio of the phosphorus content W(P) in the zinc phosphate layer to the amount of the sealing layer W(R), i.e., W(P) / W(R), is 0.3~3.

5.

3. The method for manufacturing a surface-treated metal plate according to claim 1 or 2, wherein, The process of preparing the metal substrate includes forming a zinc plating layer on the surface of the metal substrate.

4. The method for manufacturing a surface-treated metal sheet according to any one of claims 1 to 3, wherein, The zirconium content (W(Zr)) of the surface-treated metal plate is set to 1.5~23.0 mg / m³. 2 .

5. A surface-treated metal sheet, comprising: Metal substrate, A zinc phosphate layer formed on at least one side of the metal substrate, and A closed layer formed by stacking the zinc phosphate layer. The phosphorus content (W(P)) in the zinc phosphate layer is 100~300 mg / m³. 2 , The sealing layer is composed of a zirconium-containing urethane resin. The adhesion amount W(R) of the sealing layer is 60~700 mg / m³. 2 .

6. The surface-treated metal plate according to claim 5, wherein, The zirconium content (W(Zr)) is 1.5~23.0 mg / m³. 2 .

7. The surface-treated metal plate according to claim 5 or 6, wherein, The ratio of the phosphorus content W(P) in the zinc phosphate layer to the amount of the sealing layer W(R), i.e., W(P) / W(R), is 0.3~3.

5.

8. The surface-treated metal sheet according to any one of claims 5 to 7, wherein, The ratio of phosphorus content W(P) to zirconium content W(Zr) in the zinc phosphate layer, i.e., W(P) / W(Zr), is 10~120.

9. The surface-treated metal sheet according to any one of claims 5 to 8, wherein, The metal substrate includes a metal base plate and a zinc-plated layer, primarily composed of zinc. The zinc phosphate layer is formed on the zinc plating layer.

10. The surface-treated metal plate according to claim 9, wherein, The zinc content (W(Zn)) in the galvanized layer is 3~30 g / m 2 .

11. A laminated material, comprising: The surface-treated metal plate according to any one of claims 5 to 10, and A coating layer made of resin material and formed on the sealing layer.

Citation Information

Patent Citations

  • Surface treatment galvanized steel sheet excellent in appearance

    JP2017155261A